Tissue-specific expression of human CD4 in transgenic mice. - Gillespie, F P (1993)
The gene for the human CD4 glycoprotein, which serves as the receptor for human immunodeficiency virus type 1, along with approximately 23 kb of sequence upstream of the translational start site, was cloned. The ability of 5' flanking sequences to direct tissue-specific expression was tested in cell culture and in transgenic mice. A 5' flanking region of 6 kb was able to direct transcription of the CD4 gene in NIH 3T3 cells but did not result in detectable expression in the murine T-cell line EL4 or in four lines of transgenic mice. A larger 5' flanking region of approximately 23 kb directed high-level CD4 transcription in the murine T-cell line EL4 and in three independent lines of transgenic mice. Human CD4 expression in all tissues analyzed was tightly correlated with murine CD4 expression; the highest levels of human CD4 RNA expression were found in the thymus and spleen, with relatively low levels detected in other tissues. Expression of human CD4 protein in peripheral blood mononuclear cells was examined by flow cytometry in these transgenic animals and found to be restricted to the murine CD4+ subset of lymphocytes. Human CD4 protein, detected with an anti-human CD4 monoclonal antibody, was present on the surface of 45 to 50% of the peripheral blood mononuclear cells from all transgenic lines.